E-004 Cranial dural arteriovenous fistulas: asymptomatic cortical venous drainage portends less aggressive clinical course. (16th November 2010) - Strom, R; Botros, J; Refai, D; Moran, C; Cross, D; Grubb, R; Chicoine, M; Rich, K; Dacey, R; Zipfel, G; Derdeyn, C
Abstract : Objective: Cranial dural arteriovenous fistulas (dAVFs) with cortical venous drainage (CVD) (Borden type 2 and 3) are reported to carry a 15% annual risk of intracranial hemorrhage (ICH) or non-hemorrhagic neurological deficit (NHND). The purpose of this study is to compare the clinical course of type 2 and 3 dAVFs that present with ICH or NHND versus those that do not. Methods: 28 patients with type 2 or 3 dAVFs were retrospectively evaluated. CVD was classified as asymptomatic (aCVD) if patients presented incidentally or with pulsatile tinnitus or orbital phenomena. CVD was classified as symptomatic (sCVD) if patients presented with ICH or NHND. Occurrence of new ICH or new or worsening NHND between diagnosis and disconnection of CVD or last follow-up (if not disconnected) was noted. Overall frequency of events was compared using Fisher's exact test. Cumulative event free survival was compared using Kaplan–Meier analysis with log rank testing. Results: Of 17 patients with aCVD, one (5.9%) developed ICH and none experienced NHND or death during the mean 4.1 years of follow-up. Of 11 patients with sCVD, two (18.2%) developed ICH and three (27.3%) suffered new or worsened NHND over the mean 2.4 years of follow-up. One of these patients subsequently died. Overall frequency of ICH or NHND was significantly lower in patients with aCVD versus sCVD (p=0.022). Respective annual event rates were 1.4% versus 19.0%. aCVD patients had significantly higher cumulative event free survival (p=0.0016). Conclusion: Cranial dAVFs with aCVD may have a less aggressive clinical course than those with sCVD.